Epitope-Blocking Enzyme-Linked Immunosorbent Assays for Detection of West Nile Virus Antibodies in Domestic Mammals - Blitvich, Bradley J. (American Society for Microbiology, 2003)
We evaluated the ability of epitope-blocking enzyme-linked immunosorbent assays (ELISAs) to detect West Nile virus (WNV) antibodies in domestic mammals. Sera were collected from experimentally infected horses, cats, and pigs at regular intervals and screened in ELISAs and plaque reduction neutralization tests. The diagnostic efficacies of these techniques were similar.